Design to Launch. (March 2017) - Nicholson, Jamie; Breneman, Mark; Hui, Gordon
Abstract : Successful startups have learned to start building solutions early in the innovation process. If corporations could shift their focus away from costly pilot projects and instead use their resources on diverse and incremental experiments, they might be able to behave more nimbly and risk less. Large corporates that want to take advantage of new technologies tend to stand by and watch as small startups move more nimbly. Design to Launch helps big companies learn to experiment and iterate in new ways that avoid typical innovation bottlenecks.